Cryopreservation Prevents Iron-Initiated Highly Unsaturated Fatty Acid Loss during Storage of Human Blood on Chromatography Paper at −20°C. Issue 3 (7th January 2015) - Metherel, Adam H; Stark, Ken D
Abstract: Background: Fingertip prick whole blood collection on chromatography paper is amenable to high-throughput fatty acid (FA) profiling for large clinical and field studies. However, sample storage is problematic because highly unsaturated FAs (HUFAs) in erythrocytes rapidly degrade in samples stored at −20°C. Objective: The aim of the current study was to determine the mechanism of HUFA degradation and to develop prevention protocols. Methods: Free fatty acid (FFA) standards and whole blood reference material from a single participant were used to examine sample storage at −20°C for up to 90 d in triplicate. Iron chelation with deferoxamine (0–5000 μg), antioxidant protection with butylated hydroxytoluene (50 μg), cryopreservation with glycerol, and blood drying were examined using whole blood on chromatography strips. Biological replicate blood samples from additional participants ( n = 6) with a range of ω-3 (n–3) HUFA concentrations were similarly assessed. Results: FFAs were relatively stable when stored on chromatography strips at −20°C. Glycerol treatment prevented HUFA degradation in whole blood reference material for 30 d (45 ± 0.4 to 46.8 ± 0.1, means ± SDs) compared to untreated saline controls (45.9 ± 1.0 to 6.8 ± 0.2). Pretreatment of paper for blood spots with deferoxamine and drying blood before storage slowed, but not entirely prevented, HUFA degradation over 30 d to 22% and 19% below baseline, respectively, compared to 86–92% in the controls. Protection against HUFA degradation with blood drying and glycerol treatment was confirmed in the biological replicate study and confirmed by prevention of cell lysis. Conclusions: HUFA degradation during storage at −20°C appears to be due to hemolysis and subsequent iron-initiated peroxidation. This degradation may be prevented by glycerol, iron chelation, and/or dried blood spotting. A more thorough understanding of methods to prevent degradation during storage is critical with increasing use of FA profiling in large clinical studies.